Dinamika Pendidikan Karakter Peserta Didik Perkotaan Dan Pedesaan: Analisis Teori ‘Umran Ibnu Khaldun - Erdiyani, Fenny; Maimun, Maimun; Fitriyah, Eliyatul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study aims to analyze the differences in character education for students in urban and rural schools, referring to Ibn Khaldun's theory on the influence of 'umran (socio-cultural environment) in the formation of morals. The study was conducted using a comparative qualitative approach at SD QISMU (urban) and SDN Larangan Kerta (rural). Data were collected through observation, interviews, and document analysis, then analyzed using qualitative comparative analysis techniques. The results show that character education in urban areas is more formal, structured, and based on school programs with individualistic tendencies due to the influence of digital culture, but is still strengthened through religious habits and collaboration with parents. Meanwhile, character education in rural areas is more natural, communal, and rooted in religious traditions and mutual cooperation, with the important role of Kyai and local Madurese wisdom. These findings are in line with Ibn Khaldun's theory that morals are formed through habits (ta'wid) and role models (uswah) according to the social context. Thus, this study emphasizes the need for character education designs that are contextual, fair, and aligned with Islamic values and the socio-cultural dynamics of students.